2021
DOI: 10.3390/ijms22041845
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins in Immune Cells and Inflammation: New Targets for Drug Development

Abstract: The mammalian immune system senses foreign antigens by mechanisms that involve the interplay of various kinds of immune cells, culminating in inflammation resolution and tissue clearance. The ability of the immune cells to communicate (via chemokines) and to shift shape for migration, phagocytosis or antigen uptake is mainly supported by critical proteins such as aquaporins (AQPs) that regulate water fluid homeostasis and volume changes. AQPs are protein channels that facilitate water and small uncharged molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 94 publications
(105 reference statements)
0
33
0
Order By: Relevance
“…Since AQPs have been recognized as functionally involved in immune cell activity such as priming and inflammasome activation, transendothelial migration and phagocytosis, development of AQP-oriented drugs gives a promising opportunity in future therapies against metabolic diseases [ 203 ]. Up to date, several AQP modulators have been proposed and even patented for use for diagnostic and therapeutic purposes [ 295 , 296 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since AQPs have been recognized as functionally involved in immune cell activity such as priming and inflammasome activation, transendothelial migration and phagocytosis, development of AQP-oriented drugs gives a promising opportunity in future therapies against metabolic diseases [ 203 ]. Up to date, several AQP modulators have been proposed and even patented for use for diagnostic and therapeutic purposes [ 295 , 296 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most promising AQP modulators, which are relatively safe and able to effectively prevent inflammation, are the gold(III) bipyridyl compound Auphen and compounds DFP00173, Z433927330 and HTS13286. The physiological effects of their administration are summarized in [ 203 ]. An alternative AQPs-targeted approach can be based on modulation of aquaporins at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that AQPs are involved in the development of inflammatory mechanisms, supported by the detection of several isoforms in cells of both the innate and adaptive immune system and the demonstration of their dysregulation in various human diseases. For example, AQP8 downregulation was described in human Crohn’s disease and ulcerative colitis biopsies [ 38 ]. Our study showed that drug induced Aqp8 downregulation occurred in a dose dependent manner, which could lead to colon inflammation after long-term usage.…”
Section: Discussionmentioning
confidence: 99%